Breathe like a bear : 30 mindful moments for kids to feel calm and focused anytime, anywhere - Willey, Kira; Betts, Anni (Emmaus, PA : Rodale Kids, 2017)
Provides thirty exercises to help readers find calm, gain focus, and feel energized during the day, and encourages establishing a consistent mindfulness practice at home and on the go.
560L
Decoding demand: 62 (high) Semantic demand: 79 (high) Syntactic demand: 78 (high) Structure demand: 70 (high)
Keywords: Mindfulness (Psychology) -- Juvenile literature; Awareness -- Juvenile literature; Mindfulness (Psychology); Awareness